2023
DOI: 10.3390/ijms241210235
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor TaMYB30 Activates Wheat Wax Biosynthesis

Abstract: The waxy cuticle covers a plant’s aerial surface and contributes to environmental adaptation in land plants. Although past decades have seen great advances in understanding wax biosynthesis in model plants, the mechanisms underlying wax biosynthesis in crop plants such as bread wheat remain to be elucidated. In this study, wheat MYB transcription factor TaMYB30 was identified as a transcriptional activator positively regulating wheat wax biosynthesis. The knockdown of TaMYB30 expression using virus-induced gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Similar results were reported for associated shrubs, T. mongolica, and Z. xanthoxylum [29]. In contrast, the cuticular wax of rice and wheat leaves is primarily composed of 2-alcohols [42,43]. Another wax analysis for five Dianthus species revealed that C 28 1-alcohol and diketones were the major components forming the platelet-shaped and the tubular wax crystal, respectively [44].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were reported for associated shrubs, T. mongolica, and Z. xanthoxylum [29]. In contrast, the cuticular wax of rice and wheat leaves is primarily composed of 2-alcohols [42,43]. Another wax analysis for five Dianthus species revealed that C 28 1-alcohol and diketones were the major components forming the platelet-shaped and the tubular wax crystal, respectively [44].…”
Section: Discussionsupporting
confidence: 76%
“…The measurement of total wax revealed that the content in non-stressed leaves was 11.09 µg/cm 2 (Figure 2A). Compared with reported model plants and crops, the wax content in A. mongolicus leaves was approximately eight-fold of that of Arabidopsis leaves [41] and about twice that of rice and wheat leaves [42,43]. These results suggested that A. mongolicus, as a shrub adapted to desert, had a higher level of wax accumulation compared to plants thriving in mild environments, providing important support for environment adaptation through cuticle lipid structures.…”
Section: Discussionmentioning
confidence: 64%
“…Although cuticular wax accumulation in bread wheat is less understood compared with A. thaliana , wheat transcription factors governing wax accumulation have been increasingly identified in recent years. For instance, wheat AP2/ERF transcription factor TaWIN1/SHN1, basic helix-loop-helix (bHLH) transcription factor TaKPAB1, and MYB transcription factors TaMYB30, TaMYB31, and TaEPBM1/MYB96 function as positive regulators of cuticular wax accumulation [ 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the BSMV-mediated gene silencing assay, antisense fragments of TaTPR1.1, TaTPR1.2, TaDND1, TaDND2.1, and TaDND2.2 were cloned into the pCa-γbLIC vector using the primers 5 ′ -AAGGAAGTTTAGCGGGTAGCTATGGCTCTGC-3 ′ /5 ′ -AACCACCACCACCG TTGGACCCTTTCAACCTGCAC-3 ′ , 5 ′ -AAGGAAGTTTAGTGCGAACAACTTGTTTGG-3 ′ /5 ′ -AACCACCACCACCGTTGGTTGGATGACAAATCCCA-3 ′ , 5 ′ -AAGGAAGTTTACAT AAGCAAAGGCGCCATTG-3 ′ /5 ′ -AACCACCACCACGTTCATTGCCTCTCATATTGCA-3 ′ , 5 ′ -AAGGAAGTTTAGCCCGATCGCCGCCAGCCG-3 ′ /5 ′ -AACCACCACCACCGTGAC CGACCTCTCGGCGTCG-3 ′ , and 5 ′ -AAGGAAGTTTAGCCCCAGCCCCAGCTGCTG-3 ′ / 5 ′ -AACCACCACCACCGTGCTCTCCACGCGCTCGTCG-3 ′ . The BSMV-mediated gene silencing assay and microcolony index (MI) analysis were performed as described previously [56]. At least 2000 wheat-Bgt interaction sites were counted in one experiment for each treatment, and three independent biological replicates were statistically analyzed (t-test; * p < 0.05, ** p < 0.01) for each treatment.…”
Section: Bsmv-mediated Gene Silencing and Microcolony Index Analysismentioning
confidence: 99%